Public Management Theory and Practice - Raczkowski, Konrad; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
Public management is undoubtedly an acknowledged area of management science, but with meager empirical research. This book takes this challenge and presents a rare analysis of public management from the perspective of 12 Prime Ministers of Poland who governed between 1989 and 2014. The author features the concepts, practice and challenges of public management by making use of direct interviews with the Prime Ministers according to the classical management functions of planning, organization, direction and controlling. The book also presents a theoretical inquiry which redefines public management by breaking away from the traditional paradigm of public management, and introducing a 'mega-organizational' understanding of the state within new institutional economics.
State as a Special Organisation of Society -- Planning and Decision Making in Public Management -- State Organisation for Institutional and Systemic Perspective -- Managing and Leading in Public Organisations -- Control and its Regulative Function in Public Management -- Governance and Public Management Practice in Poland.
Keywords: Public administration; Public policy; Public relations; Business ethics